Emotional awareness and expression therapy (EAET) for chronic pain following traumatic orthopaedic injury and surgery: study protocol for a single-arm feasibility clinical trial - Renan Castillo; Stephen Wegener; Mark A Lumley; Claudia Campbell; Scott G Ravyts; Nicolette Carnahan; Fenan S Rassu; Rachel Aaron (BMJ Open)
Background Nearly half of individuals who sustain orthopaedic trauma develop chronic pain and experience significant levels of depression and anxiety. Emotional awareness and expression therapy (EAET) is a newly developed psychological intervention designed to treat chronic pain by helping patients process psychological trauma and conflict to reduce pain. The purpose of this study is to examine the feasibility of delivering EAET to individuals who sustained traumatic orthopaedic injuries requiring surgery and who have chronic pain 6 months after hospital discharge.Methods and analysis The study will consist of a single-arm design. Thirty individuals who sustained traumatic orthopaedic injuries requiring surgery and who reported chronic pain 6 months after hospital discharge will be recruited. Participants will receive eight sessions of individually administered EAET delivered via telehealth and complete self-report questionnaires at three timepoints (pretreatment, post-treatment and 3-month follow-up). Quantitative sensory testing will also be done before and after treatment. The primary outcome of the study is feasibility (eg, per cent of eligible patients recruited and per cent of study completers) and acceptability as reported by responses to a self-report questionnaire.Ethics and dissemination This study has been approved by the Johns Hopkins Institutional Review Board. All data are expected to be collected by 2026, with results of this study to be disseminated via relevant peer-reviewed journals and scientific conferences.Trial registration number ClinicalTrials.gov NCT05989230. Registered on 14 August 2023.